1963
DOI: 10.1172/jci104692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Time Available and the Time Required for Co2 Equilibration in the Lung*

Abstract: We have previously shown that the injection of sodium bicarbonate into the pulmonary artery of a dog enclosed in a body plethysmograph results in the evolution of gas in the alveoli which is measurable as an increase in the pressure in the plethysmograph (1). By comparing the time elapsed between injection and gas evolution following injection of a bicarbonate solution with the analogous time interval following injection of an inert gas, ether (2), a value for the over-all rate of the reactions leading to CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1966
1966
1990
1990

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…Dimensions and dynamics of CO2 stores in the lungs of man. The data presented above support the findings of a number of investigators (3)(4)(5), that the various forms of carbon dioxide present in the lungs exchange so rapidly, that the alveolar Pco2 can be considered to come from one common CO2 pool. Representative figures for an adult human with a resting lung volume of 3000-ml STPD at an alveolar Pco2 of 40 mm Hg are: 150 ml of CO2 in the alveolar gas, 200 ml of CO2 in the pulmonary tissue (Vti.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Dimensions and dynamics of CO2 stores in the lungs of man. The data presented above support the findings of a number of investigators (3)(4)(5), that the various forms of carbon dioxide present in the lungs exchange so rapidly, that the alveolar Pco2 can be considered to come from one common CO2 pool. Representative figures for an adult human with a resting lung volume of 3000-ml STPD at an alveolar Pco2 of 40 mm Hg are: 150 ml of CO2 in the alveolar gas, 200 ml of CO2 in the pulmonary tissue (Vti.…”
Section: Discussionsupporting
confidence: 84%
“…They concluded that the interconversion of the various forms of The Journal of Clinical Investigation Volume 47 1968CO2 is so rapid that the expired CO2 may be considered to come from one large common CO2 pool. Similar conclusions were reached by Feisal, Sackner, and DuBois who injected bicarbonate into the pulmonary artery of the dog and measured the evolution of CO2 in the alveoli with a sensitive body plethysmograph (5). These investigators as well as others have found that inhibition of the enzyme carbonic anhydrase modified the exchange of CO2 between blood, pulmonary tissues, and alveolar gas sufficiently to produce a significant alveolar to end-capillary CO2 gradient (A-C CO2 gradient) (6)(7)(8).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Therefore, Ooshima et al (1977) could not find out the linear correlation between RCA activity and acid-base balance. As Feisal et al (1963), Klocke (1978) and Nagal et al (1974) reported that RCA activity affects the Pco2 level, it is thought that the RCA activity also has a correlation with Pco2 which changes in parallel with pH and HC03-/Pco2 ratio through the Henderson-Hasselbalch formula.…”
Section: Experiments In Vivomentioning
confidence: 98%